Impact of Serum Estradiol Levels Prior to Progesterone Administration in Artificially Prepared Frozen Embryo Transfer Cycles - Mackens, Shari; Santos-Ribeiro, Samuel; Orinx, Ellen; De Munck, Neelke; Racca, Annalisa; Roelens, Caroline; Popovic-Todorovic, Biljana; De Vos, Michel; Tournaye, Herman; Blockeel, Christophe (Frontiers in Endocrinology, 2020)
Background The need for endocrine monitoring in artificial cycles for frozen embryo transfer (FET) remains unclear and, more specifically, the value of the late-proliferative phase serum estradiol (E2) levels is with conflicting evidence in current literature. Objective To investigate whether artificial FET cycles require endocrine monitoring for the serum E2 level prior to initiation of exogenous progesterone administration after an endometrial thickness of 6.5 mm has been reached. Design One thousand two hundred and twenty-two (n=1222) artificial FETs performed in a tertiary centre between 2010-2015 were subdivided into 3 groups according to the following late-proliferative serum E2 level percentiles: ≤p10 (E2 ≤144 pg/ml; n=124), p11 – p90 (E2 from 145 to 438 pg/ml; n=977) and >p90 (E2 >439 pg/ml; n=121). A mixed-effects multilevel multivariable regression analysis was performed to assess the potential effect of the late-proliferative E2 level on the live birth rate (LBR). Results The level of late-proliferative circulating E2 showed no significant difference in terms of LBR after FET. Specifically, the multivariable regression model demonstrated a LBR of 19.5% for the p11-p90 reference group, compared to 24.4% for the ≤p10 (p=0.251) and 19.5% for the >p90 group (p=0.989). Conclusion In this large retrospective dataset, no association was observed between late-proliferative phase serum E2 levels and LBR following FET in artificially prepared cycles. Although, caution is warranted due to the retrospective nature of the analysis and the potential for unmeasured confounding, we argue that monitoring of the late-proliferative serum E2 levels and using them to guide clinical decision-making (e.g. medication step-up, cycle prolongation or cancelation) may be of questionable value.